DIGITAL-BASED ISLAMIC RELIGIOUS EDUCATION LEARNING MEDIA: ANALYSIS OF IMPLEMENTATION, CHALLENGES AND OPPORTUNITIES IN JUNIOR HIGH SCHOOLS - Faqihuddin, Achmad; Muflih, Abdillah (Universitas Pendidikan Indonesia, 2024)
AbstractThis study analyzes the implementation, challenges, and opportunities of using digital-based learning media in Islamic Religious Education (PAI) in Junior High Schools (SMP) in Bandung. Using a qualitative approach, data were collected through in-depth interviews with 17 PAI teachers from 17 SMPs. The results showed that although conventional learning media such as textbooks and whiteboards are still dominant, there has been a significant increase in digital media such as PowerPoint, videos, and interactive applications such as Quizizz and Wordwall. Internal challenges teachers face include limited technological knowledge, resistance to change, time constraints, and dependence on traditional teaching methods. External challenges include more technological infrastructure, internet network problems, and limited resources. Nevertheless, integrating digital media offers excellent opportunities to improve the quality of learning, develop 21st-century skills, and prepare students for the digital era. This study recommends comprehensive strategies such as teacher training and professional development, institutional support in providing technological infrastructure, and collaboration between teachers, schools, government, and other stakeholders.Keywords: Learning Media, Digital, Islamic Religious Education, Quality of Learning, Junior High SchoolAbstrakPenelitian ini menganalisis implementasi, tantangan, dan peluang penggunaan media pembelajaran berbasis digital dalam Pendidikan Agama Islam (PAI) di Sekolah Menengah Pertama (SMP) di Bandung. Menggunakan pendekatan kualitatif, data dikumpulkan melalui wawancara mendalam dengan 17 guru PAI dari 17 SMP yang berbeda. Hasil penelitian menunjukkan bahwa meskipun media pembelajaran konvensional seperti buku paket dan papan tulis masih dominan, terdapat peningkatan signifikan dalam penggunaan media digital seperti PowerPoint, video, dan aplikasi interaktif seperti Quizizz dan Wordwall. Tantangan internal yang dihadapi guru meliputi keterbatasan pengetahuan teknologi, resistensi terhadap perubahan, keterbatasan waktu, dan ketergantungan pada metode pengajaran tradisional. Tantangan eksternal mencakup kurangnya infrastruktur teknologi, masalah jaringan internet, dan keterbatasan sumber daya. Meskipun demikian, integrasi media digital menawarkan peluang besar untuk meningkatkan kualitas pembelajaran, mengembangkan keterampilan abad ke-21, dan mempersiapkan siswa menghadapi era digital. Studi ini merekomendasikan strategi komprehensif seperti pelatihan dan pengembangan profesional bagi guru, dukungan institusional dalam penyediaan infrastruktur teknologi, serta kolaborasi antara guru, sekolah, pemerintah, dan pemangku kepentingan lainnya. Kata kunci : Media Pembelajaran, Digital, Pendidikan Agama Islam, Mutu Pembelajaran, SMP